PENGARUH PENGUNGKAPAN AKUNTANSI LINGKUNGAN, OWNERSHIP DISPERSION, DAN GCG (GOOD CORPORATE GOVERNANCE) TERHADAP KINERJA LINGKUNGAN: (Pada Perusahaan Energi Sub Sektor Minyak, Gas, dan Batu Bara yang Terdaftar di BEI Tahun 2021-2023) - Tania, Tessa Eka (Jurnal Nirta : Inovasi Multidisiplin, 2025)
Abstract.i This study was conducted to determine the effect of environmental accounting disclosure, ownership dispersion, and the implementation of Good Corporate Governance (GCG) on environmental performance in energy companies in the oil, gas and coal sub-sectors listed on the IDX for the 2021-2023 period. Environmental performance is measured based on sustainability reports by looking at the level of PROPER awards and GRI standards disclosed by the company. The research method applied is a quantitative approach that tests the results with analysis using the SmartPLS 4 application through the Outer Model and Inner Model Tests. Information is taken from annual reports and sustainability reports of companies listed on the IDX. The results of this study explain that environmental accounting disclosures contribute significantly and positively to environmental performance, reflecting transparency that encourages more responsible business practices. Ownership dispersion contributes significantly by encouraging better managerial oversight through diversification of shareholder interests. In addition, GCG implementation has no effect on environmental performance.